PERAN LITERASI DIGITAL DALAM MEMODERASI PENGARUH DOOM SPENDING, DOOM SCROLING DAN FEAR OF MISSING OUT TERHADAP PERILAKU PENGELOLAAN KEUANGAN GENERASI Z DI KOTA KUPANG - Hernawati, Retno; Manek, Alfridus Mau; Sasea, Tirtania (Among Makarti, 2025)
Abstract : This study aims to analyze (1) the influence of Doom Spending, Doom Scrolling, and Fear of Missing Out on the financial management behavior of Generation Z in Kupang City and (2) the role of digital literacy in moderating the relationship between Doom Spending, Doom Scrolling, and Fear Of Missing Out with the financial management behavior of this generation. The sampling technique used was purposive sampling, with a total of 398 respondents. Data analysis was carried out using multiple linear regression and Moderated Regression Analysis (MRA). The results of the study show that Doom Spending, Doom Scrolling, and Fear Of Missing Out have an influence on the financial management behavior of Generation Z in Kupang City. In addition, digital literacy has been shown to moderate the relationship between Doom Scrolling and Fear Of Missing Out and financial management behavior, but it does not act as a moderator in the relationship between Doom Spending and financial management behavior of Generation ZAbstrak : Penelitian ini bertujuan untuk menganalisis (1) pengaruh Doom Spending, Doom Scrolling, dan Fear of Missing Out terhadap perilaku pengelolaan keuangan Generasi Z di Kota Kupang serta (2) peran literasi digital dalam memoderasi hubungan antara Doom Spending, Doom Scrolling, dan Fear Of Missing Out dengan perilaku pengelolaan keuangan generasi tersebut. Teknik pengambilan sampel yang digunakan adalah purposive sampling, dengan jumlah responden sebanyak 398 orang. Analisis data dilakukan menggunakan regresi linear berganda serta Moderated Regression Analysis (MRA). Hasil penelitian menunjukkan bahwa Doom Spending, Doom Scrolling, dan Fear Of Missing Out memiliki pengaruh terhadap perilaku pengelolaan keuangan Generasi Z di Kota Kupang. Selain itu, literasi digital terbukti mampu memoderasi hubungan antara Doom Scrolling dan Fear Of Missing Out dengan perilaku pengelolaan keuangan, namun tidak berperan sebagai moderator dalam hubungan antara Doom Spending dan perilaku pengelolaan keuangan Generasi Z